Algorithms and architectures from parallel processing : 15th International Conference, ICA3PP 2015, Zhangjiajie, China, November 18-20, 2015. Proceedings /: 15th International Conference, ICA3PP 2015, Zhangjiajie, China, November 18-20, 2015. Proceedings. ([2015]) - Unknown
No abstract available